Draft Genome Sequences of Basidiomycetous Epiphytic Phylloplane Yeast Type Strains Dioszegia crocea JCM 2961 and Dioszegia aurantiaca JCM 2956 - Takashima, Masako (Microbiol Resour Announc, 2019)
We report the draft genome sequences of type strains for Dioszegia crocea and its closely related species Dioszegia aurantiaca, which should improve our understanding of the epiphytic phylloplane yeasts. These data will also have implications for the plant microbiome, since Dioszegia is considered a microbial “hub” taxon.